Legal Protection Of Traditional Medicines In The Perspective Of Health Law And Intellectual Property Law In Indonesia - Susanti, Susi; Putri, Yunita Maya; Havez, Muhammad (Universitas Malayati, 2024)
Advancements in health law mirror the progress made in health science. Presently, health law holds significant weight in addressing diverse challenges and legal matters within the health domain. Conversely, amidst the evolution of increasingly sophisticated technology, traditional medicine has garnered diminished attention. Yet, within the context of Indonesia's efforts to ensure the right to health, traditional medicine ought to be a crucial alternative to be acknowledged. This proposition finds support in Indonesia's rich natural environment, which boasts abundant biodiversity, including numerous plant species with potential applications in traditional medicinal practices. Consequently, ensuring legal safeguards for traditional medicines from the perspectives of both health law and intellectual property law becomes paramount. The research methodology adopted in this study is normative research, centered on the conceptualization of legislative principles or norms serving as the foundation for human conduct. The primary objective is to scrutinize the Legal Protection of Traditional Medicines within the framework of Health Law and Intellectual Property Law in Indonesia.The study's findings revealed that while Law No. 17 of 2023 does not explicitly delineate traditional medicine, it equates the term with